Business Strategies Used by Some Educational Entrepreneurs for Survival during the Covid-19 Pandemic - Constance Chifamba (Current Aspects in Business, Economics and Finance Vol. 4, 2022)
The aim of this chapter is to summarize lessons from lived experiences (phenomenological study) of purposively selected education entrepreneurs in Harare during the Covid-19 pandemic. These important lessons (themes) include opening new business opportunities for educational entrepreneurs, job creation in ICT, professional development and development of resilience. The study recommends that since the Covid-19 Pandemic is unique and has an evolving nature, educational entrepreneurs should shift their focus from simply mitigating and focus on proactively developing entrepreneurial innovativeness and adaptability skills in order to cope with a future that is inherently unpredictable. This in turn develops resilience, bolsters confidence and enhances readiness to respond assertively and flexibly in the face crisises.